Nano-sized metal-organic frameworks: Synthesis and applications - Cai, Xuechao; Xie, Zhongxi; Li, Dandan; Kassymova, Meruyert; Zang, Shuang-Quan; Jiang, Hai-Long (Coordination chemistry reviews, 2020)
Nano-sized metal-organic frameworks (nanoMOFs), which give rise to the discovery of a variety of properties not observed in their bulk counterparts, have attracted tremendous attention. In this review, we first summarize the synthetic strategies of uniform and monodispersed MOF nanoparticles as well as the 1-D nanofibers that are assembled by 0-D MOF nanoparticles. Whereafter, the intrinsic size-related properties towards the most important applications including bio-imaging, drug delivery, photodynamic therapy (PDT), photothermal therapy (PTT), catalysis, energy and membrane separation are highlighted as well. Furthermore, the challenges and future prospects of the synthesis and applications of nanoMOFs are briefly discussed, which we hope will contribute to further push the development of nanoMOF science. [Display omitted] •An overview of the synthesis of nanoMOFs and their one-dimensional nanomaterials.•Applications of nanoMOFs in the fields of biomedicine, catalysis, energy and membrane separation.•The challenges and opportunities for the synthesis and application of nanoMOFs. Recently, nanoscale metal-organic frameworks (nanoMOFs), which leads to the discovery of a variety of properties not observed in their bulk counterparts, have attracted tremendous attention. To be specific, while possessing the properties of bulk MOF materials including high surface area, structural diversity and tailorability etc., nanoMOFs also have some unique advantages, such as accelerated adsorption/desorption kinetics and accessibility to the internal active sites. Moreover, due to their very small sizes and good biocompatibility, nanoMOFs have been widely investigated in biomedicine. In addition, not limited to MOF nanoparticles, their assembly to MOF-based 1-D nanomaterials have also been investigated for catalysis, energy and membrane separation applications. In this review, we first summarize the synthetic strategies of uniform and monodisperse nanoMOFs, and then the intrinsic size-dependent properties towards the most important applications are highlighted as well. Furthermore, the challenges and future prospects of the synthesis and application of nanoMOFs are briefly provided, which we hope will contribute to further push the development of nanoMOF science.